Mapping the Methodological Quality of International Primary-Secondary Transitions Research Literature: A Systematic Methodological Review - Hannah, Elizabeth F. S.; Barlow, William D.; Bagnall, Charlotte; Jindal-Snape, Divya (International Journal of Educational and Life Transitions, 2023)
This is the first systematic methodological review undertaken of international primary-secondary transitions empirical research. It sought to understand and rate the researcher/s’ congruence between their: stated philosophical perspective and methodology; conceptualisation of transitions and methodology; theorisation of transitions and methodology; and the overall quality and rigour of the research. The literature review covered the period 2008–2021. A review of reviews ascertained that no previous studies focused on either the congruence between researcher/s’ philosophical stance nor their theorisation of transitions with research methodology. Only one review briefly noted the importance of the congruence between transitions conceptualisation and methodology. Therefore, this review is unique in its purpose and internationally significant.Five data bases were searched applying specific inclusion criteria (e.g., peer reviewed empirical papers, international, covering the period 2008–2021) resulting in 151 papers. A rigorous and systematic approach was adopted throughout all stages of the research process (searching, screening, describing and mapping, and quality appraisal). 74 papers were cross-checked for quality assurance purposes. A self-developed assessment framework was used in the first phase of analysis. The next phase involved the use of the Mixed Methods Appraisal Tool to assess methodological quality.Findings indicate that approximately 91% of papers did not state their philosophical perspective. Two thirds of researchers did not provide their conceptualisation of transitions and 59% failed to provide their theoretical perspective. Those studies which offered their conceptualisation and theorisation of transitions were of a higher quality than those which only indicated their conceptualisation or theorisation of transitions.These findings have implications for researchers to state their conceptualisation and theorisation of transitions. Policy makers and practitioners should be aware of how they understand and action primary-secondary transitions research. As such, this paper provides a unique insight and makes an original and significant contribution to the field.
Keywords: Primary-secondary transitions; mapping; methodology; congruence